The eyes & the impossible - Eggers, Dave (Alfred A. Knopf, 2023)
Free dog Johannes' job is to observe everything that happens in his urban park and report back to the park's three bison elders, but changes are afoot, including more humans, a new building, a boatload of goats, and a shocking revelation that changes his view of the world.